Implementation and Training of Linux-Based Network Administration to Enhance Network Infrastructure - Izulhak Algi Fahrizal; Andi Rakhmat Baharuddin (Computer Engineering and Applications Journal, 2026)
This article aims to comprehensively synthesize the relationship between Linux server implementation, network administration training, and their impact on network infrastructure improvement. Linux servers are becoming increasingly important in modern network management because they support service flexibility, resource efficiency, security, automation, and high availability, while network administration training is a key factor in building the technical competencies of network administrators. This study employs a systematic review method on 35 scientific articles classified into three main topics: Linux server implementation, network administration training, and the impact on network infrastructure. The review results indicate that Linux server implementation contributes to improved performance, stability, efficiency, and reliability of network services, whereas hands-on training plays a role in enhancing administrators’ operational skills and readiness. These findings confirm that improvements in Linux server-based network infrastructure depend on the integration of the quality of technical implementation and the competencies of the personnel managing it.